The Salmonella effector protein SpvC, a phosphothreonine lyase is functional in plant cells - Neumann, Christina; Fraiture, Malou; Hernàndez-Reyes, Casandra; Akum, Fidele N.; Virlogeux-Payant, Isabelle; Chen, Ying; Pateyron, Stephanie; Colcombet, Jean; Kogel, Karl-Heinz; Hirt, Heribert; Brunner, Frédéric; Schikora, Adam (Frontiers in Microbiology, 2014)
Salmonella is one of the most prominent causes of food poisoning and growing evidence indicates that contaminated fruits and vegetables are an increasing concern for human health. Successful infection demands the suppression of the host immune system, which is often achieved via injection of bacterial effector proteins into host cells. In this report we present the function of Salmonella effector protein in plant cell, supporting the new concept of trans-kingdom competence of this bacterium. We screened a range of Salmonella Typhimurium effector proteins for interference with plant immunity. Among these, the phosphothreonine lyase SpvC attenuated the induction of immunity-related genes when present in plant cells. Using in vitro and in vivo systems we show that this effector protein interacts with and dephosphorylates activated Arabidopsis Mitogen-activated Protein Kinase 6 (MPK6), thereby inhibiting defense signaling. Moreover, the requirement of Salmonella SpvC was shown by the decreased proliferation of the ΔspvC mutant in Arabidopsis plants. These results suggest that some Salmonella effector proteins could have a conserved function during proliferation in different hosts. The fact that Salmonella and other Enterobacteriaceae use plants as hosts strongly suggests that plants represent a much larger reservoir for animal pathogens than so far estimated.